ANALISIS BENTUK PENAMPANG BULAT, SEGI EMPAT DAN BULAT BERONGGA TERHADAP FATIGUE FAILURE DAN TEGANGAN PADA MATERIAL BAJA ST 60 - Aspiyansyah, Aspiyansyah; Widayat, Adriant (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Metal fatigue is a problem in the use of metals in their applications, especially when they are exposed to cyclic or repetitive loads. This study analyzes the effect of round, rectangular and spherical cross-sections on fatigue failure of ST 60 steel. By providing a fatigue test load of 150 N and a rotating speed of 1500 rpm and a test specimen installation position with a distance of 70 cm, it was found that the round cross-section broke when experiencing 26,471 cycles, the rectangular cross-sectional shape broke when experiencing 115,515 cycles and the hollow round shape broke when experiencing 201,983 cycles. The largest shear stress is generated by a spherical cross-section with a value of 247.7 N/mm2 and the lowest is by a material with a hollow spherical cross-section with a value of 194.478 N/mm2. Normal stress and the highest shear stress are produced specimens with a spherical cross-sectional shape, this is because the spherical cross-section has a tendency to spread normal stress evenly over its surface.